Three Bryophyte Species New to Türkiye and Southwest Asia (Bangladesh Journal of Plant Taxonomy, 2024)
As a result of extensive bryophyte surveys across the different parts of the Karçal Mountain, Türkiye's first biosphere reserve area, Artvin region (Caucasus) in the East Black Sea region of Türkiye, Jungermannia pumila, Scapania uliginosa and Heterocladium flaccidum found as new to Türkiye. Moreover, these taxa are the first time reported for bryophyte flora of South-West Asia in this paper. Descriptions, illustrations, distributions, ecological characteristics, and comparisons with morphologically similar taxa were also provided.Bangladesh J. Plant Taxon. 31(1): 25-32, 2024 (June)